Introducing Mobile Money in Rural Mozambique: Evidence from a Field Experiment* - Batista, Cátia (2014)
The limitations of access to finance in Africa, together with the recent boom in cell phone use in that continent, created high expectations regarding the introduction of mobile money in many African countries. The success story of M-PESA in Kenya raised the bar further. We designed and conducted a field experiment to assess the impact of randomized mobile money dissemination in rural Mozambique. For this purpose we benefit from the fact that mobile money was only recently launched in the country, allowing for the identification of a pure control group. This paper reports on the first results of this ongoing project after the first wave of dissemination efforts in rural locations, which included the recruitment and training of mobile money agents, community meetings and theaters, as well as individual rural campaigning. Administrative and behavioral data both show clear adherence to the services in the treatment group. Financial literacy and trust outcomes are also positively affected by the treatment. We present behavioral evidence that the marginal willingness to remit was increased by the availability of mobile money. Finally, we observe a tendency for mobile money to substitute traditional alternatives for both savings and remittances.